Let G be a finite abelian group with exponent exp(G) and S be a sequence with elements of G. We say S is a zero-sum sequence if the sum of the elements in S is the zero element of G. For a positive integer t, let stexp(G)(G) (respectively, s′texp(G)(G)) denote the smallest integer ℓ such that every sequence (respectively, zero-sum sequence) S over G with |S|≥ℓ contains a zero-sum subsequence of length texp(G). The invariant stexp(G)(G) (respectively, s′texp(G)(G)) is called the Generalized Erdős-Ginzburg-Ziv constant (respectively, Modified Erdős-Ginzburg-Ziv constant) of G. In this paper, we discuss the relationship between Generalized Erdős-Ginzburg-Ziv constant and Modified Erdős-Ginzburg-Ziv constant, and determine s′texp(G)(G) for some finite abelian groups.
Citation: Yuting Hu, Jiangtao Peng, Mingrui Wang. On Modified Erdős-Ginzburg-Ziv constants of finite abelian groups[J]. AIMS Mathematics, 2023, 8(3): 6697-6704. doi: 10.3934/math.2023339
[1] | Guoqing Wang . A generalization of Kruyswijk-Olson theorem on Davenport constant in commutative semigroups. AIMS Mathematics, 2020, 5(4): 2992-3001. doi: 10.3934/math.2020193 |
[2] | Guoqing Wang . Lower bound for the Erdős-Burgess constant of finite commutative rings. AIMS Mathematics, 2020, 5(5): 4424-4431. doi: 10.3934/math.2020282 |
[3] | Xiao-Yu Li, Yu-Lan Wang, Zhi-Yuan Li . Numerical simulation for the fractional-in-space Ginzburg-Landau equation using Fourier spectral method. AIMS Mathematics, 2023, 8(1): 2407-2418. doi: 10.3934/math.2023124 |
[4] | Narcisse Batangouna . A robust family of exponential attractors for a time semi-discretization of the Ginzburg-Landau equation. AIMS Mathematics, 2022, 7(1): 1399-1415. doi: 10.3934/math.2022082 |
[5] | Huiqing Wang, Md Nur Alam, Onur Alp İlhan, Gurpreet Singh, Jalil Manafian . New complex wave structures to the complex Ginzburg-Landau model. AIMS Mathematics, 2021, 6(8): 8883-8894. doi: 10.3934/math.2021515 |
[6] | Guixin Deng, Shuxin Wang . On the Davenport constant of a two-dimensional box [[−1,1]]×[[−m,n]]. AIMS Mathematics, 2021, 6(2): 1101-1109. doi: 10.3934/math.2021066 |
[7] | Mourad S. Semary, M. T. M. Elbarawy, Aisha F. Fareed . Discrete Temimi-Ansari method for solving a class of stochastic nonlinear differential equations. AIMS Mathematics, 2022, 7(4): 5093-5105. doi: 10.3934/math.2022283 |
[8] | Junling Sun, Xuefeng Han . Existence of Sobolev regular solutions for the incompressible flow of liquid crystals in three dimensions. AIMS Mathematics, 2022, 7(9): 15759-15794. doi: 10.3934/math.2022863 |
[9] | Rui Wang, Jiangtao Peng . On the inverse problems associated with subsequence sums of zero-sum free sequences over finite abelian groups Ⅱ. AIMS Mathematics, 2021, 6(2): 1706-1714. doi: 10.3934/math.2021101 |
[10] | Muhammad Imran Asjad, Sheikh Zain Majid, Waqas Ali Faridi, Sayed M. Eldin . Sensitive analysis of soliton solutions of nonlinear Landau-Ginzburg-Higgs equation with generalized projective Riccati method. AIMS Mathematics, 2023, 8(5): 10210-10227. doi: 10.3934/math.2023517 |
Let G be a finite abelian group with exponent exp(G) and S be a sequence with elements of G. We say S is a zero-sum sequence if the sum of the elements in S is the zero element of G. For a positive integer t, let stexp(G)(G) (respectively, s′texp(G)(G)) denote the smallest integer ℓ such that every sequence (respectively, zero-sum sequence) S over G with |S|≥ℓ contains a zero-sum subsequence of length texp(G). The invariant stexp(G)(G) (respectively, s′texp(G)(G)) is called the Generalized Erdős-Ginzburg-Ziv constant (respectively, Modified Erdős-Ginzburg-Ziv constant) of G. In this paper, we discuss the relationship between Generalized Erdős-Ginzburg-Ziv constant and Modified Erdős-Ginzburg-Ziv constant, and determine s′texp(G)(G) for some finite abelian groups.
Let Zn denote the cyclic group of n elements. Let G be a finite abelian group. Up to isomorphism, we can write G as Zn1⊕…⊕Znr with 1<n1∣…∣nr, where nr=exp(G) is the exponent of G. Whenever n1=n2=⋯=nr=n, we denote G by Zrn. For convenience, we write g∈Zrn as g=(a1,a2,…,ar), where integers ai∈[0,n−1] for every i∈[1,r].
Let G be an abelian group and G0⊆G be a subset. We consider sequences over G0 as elements in the free abelian monoid with basis G0. So a sequence S over G0 can be written in the form
S=g1⋅…⋅gℓ=∏g∈G0gvg(S), |
where vg(S)∈N∪{0} denotes the multiplicity of g in S. We denote |S|=ℓ∈N∪{0} the length of S, σ(S)=∑ℓi=1gi=∑g∈Gvg(S)g∈G the sum of S. We say the sequence S over G0 is a zero-sum sequence if σ(S)=0∈G. For an element g∈G, let g+S denote the sequence (g+g1)⋅…⋅(g+gℓ) over g+G0. Let H be a subgroup of G and φ:G→G/H be the natural homomorphism. Then φ(S) denotes the sequence φ(g1)⋅…⋅φ(gℓ) over G0/H. A sequence T is called a subsequence of S if vg(T)≤vg(S) for all g∈G0. Whenever T is a subsequence of S, let ST−1 denote the subsequence with T deleted from S. If S1 and S2 are two sequences over G, let S1S2 denote the sequence satisfying that vg(S1S2)=vg(S1)+vg(S2) for all g∈G0. If S1=S2, we denote S1S2 by S21.
For a finite abelian group G and a positive integer t, let stexp(G)(G) denote the smallest integer ℓ such that every sequence S over G with |S|≥ℓ contains a zero-sum subsequence of length texp(G). For t=1, we abbreviate sexp(G)(G) to s(G), which is called the Erdős-Ginzburg-Ziv constant of G. For t≥2, the invariant stexp(G)(G) is called the Generalized Erdős-Ginzburg-Ziv constant of G. The classical Erdős-Ginzburg-Ziv Theorem [7], proved in 1961, states that
s(Zn)=2n−1. |
This theorem was viewed as one of the starting points for many problems involving zero-sum sequences over finite abelian groups. These problems occur naturally in various branches of combinatorics and number theory (see [1,3,16] for some classical papers). Since 1960s, the invariant stexp(G)(G) has been studied by many authors (for recent progress see [6,10,12,13,14,15,17,18,19,20]).
Our main motivation of this paper is the following Modified Erdős-Ginzburg-Ziv constant, which was introduced by Augspurger et al. [2] in 2017.
Definition 1.1. Let G be an abelian group and G0⊆G be a subset. For a positive integer w, let s′w(G0) denote the smallest integer ℓ such that every zero-sum sequence S over G0 with |S|≥ℓ contains a zero-sum subsequence of length w. If no such ℓ exists, then let s′w(G0)=∞. For w=exp(G), we abbreviate s′exp(G)(G0) to s′(G0). The invariant s′w(G0) is called the Modified Erdős-Ginzburg-Ziv constant of G0.
There has been lots of results on Generalized Erdős-Ginzburg-Ziv constant, but little is known about Modified Erdős-Ginzburg-Ziv constant.
For the infinite abelian group Z, let [−k,k]={i∣−k≤i≤k}⊂Z, where k is a positive integer. Augspurger et al. [2] gave some conditions for which s′w([−k,k]) is finite. They also gave the first results on s′w([−k,k]) for some positive integers w,k. In 2019, Berger [4] completely determined s′w([−k,k]) for all positive integers w,k.
Let G be a finite abelian group and g be an element of G with ord(g)=exp(G). Let w be a positive integer with exp(G)∤w. Then for every positive integer ℓ, both S1=gℓ⋅(−ℓg) and S2=gℓ+1⋅(−(ℓ+1)g) are zero-sum sequences over G. But either S1 or S2 contains no zero-sum subsequence of length w. It follows that s′w(G) is infinite. So we always consider the case when w=texp(G), where t is a positive integer. In 2009, Berger and Wang [5] determined the invariants s′tn(Zn) for every positive integer t and s′(Z2n).
By the definition of stexp(G)(G) and s′texp(G)(G), we clearly have
s′texp(G)(G)≤stexp(G)(G) | (1.1) |
for every finite abelian group G and every positive integer t.
Let G be a finite abelian group. In 2017, Zhong (see [2,Lemma 1]) proved that if gcd(s(G)−1,exp(G))=1, then s′(G)=s(G). In this paper, we can slightly improve this result as
Theorem 1.2. Let G be a finite abelian group. If gcd(stexp(G)(G)−i,exp(G))=1 for some positive integer i, then s′texp(G)(G)>stexp(G)(G)−i. Moreover, if gcd(stexp(G)(G)−1,exp(G))=1, then s′texp(G)(G)=stexp(G)(G).
By Theorem 1.2, we are able to determine s′texp(G)(G) for the following cases.
Theorem 1.3. (1) Let G=Z2n. If t≥2 and gcd(n,3)=1, then s′tn(G)=stn(G)=tn+2n−2.
(2) Let G=Zm⊕Zn with 1≤m∣n. If gcd(2m−i,n)=1 for some integer i≥4, then s′(G)≥2m+2n−(i−1). Moveover, if i=4, then s′(G)=s(G)=2m+2n−3.
(3) Let G=Zd2, where d is even. If 2t>d, then s′2t(G)=s2t(G)=2t+d.
We also find some cases such that s′texp(G)(G)≠stexp(G)(G). We need the following definition associated with s(G).
Definition 1.4. [8,Definition 1.1] A pair (n,d) of positive integers is said to have Property D if (n−1)∣(s(Zdn)−1) and every sequence S over Zdn of length s(Zdn)−1 having no zero-sum subsequence of length n is of the form Tn−1, where T is a sequence over Zdn with |T|=(s(Zdn)−1)/(n−1).
Let G=Zrn with n≥3 and r≥2. Suppose s(G)=c(n−1)+1 for some positive integer c and (n,r) has Property D. Zhong (see [2,Lemma 1]) proved that if gcd(s(G)−1,n)=c, then s′(G)<s(G). In this paper, we obtain that
Theorem 1.5. (1) Let n,d,k1 be positive integers and n>1. Suppose s(Zdnk)=c(nk−1)+1 for every positive integer k, where c is a constant depending only on n and d. If s′(Zdnk1)≤s(Zdnk1)−i for some positive integer i, then s′(Zdnk)≤s(Zdnk)−i for every integer k≥k1.
(2) Let G=Zm⊕Zn with 1≤m∣n and H=Zd⊕Zd with d∣m. If s′(H)≤s(H)−i for some positive integer i, then s′(G)≤s(G)−i.
By using Theorem 1.2 and Theorem 1.5, we obtain the following results.
Theorem 1.6. Let k,d be two positive integers.
(1) If k<d, then s′(Zd2k)=s(Zd2k)=2d(2k−1)+1.
(2) If k≥d, then s′(Zd2k)=s(Zd2k)−1=2d(2k−1).
(3) If k≥2, then s′(Z33k)=s(Z33k)−1=9(3k−1).
We remark that the first two results in Theorem 1.6 confirm a conjecture of Berger and Wang (see [5,Conjecture 4.2]).
This paper is organized as follows. In Section 2, we deal with Theorems 1.2 and 1.3. In Section 3, we prove Theorems 1.5 and 1.6. In the final section, some additional results are given.
In this section, we deal with some cases when s′texp(G)(G)=stexp(G)(G).
Proof of Theorem 1.2. Suppose gcd(stexp(G)(G)−i,exp(G))=1 for some positive integer i. We need to find a zero-sum sequence of length stexp(G)(G)−i, which contains no zero-sum subsequence of length texp(G). By the definition of stexp(G)(G), there exists a sequence S with |S|=stexp(G)(G)−i and S has no zero-sum subsequence of length texp(G). Assume that σ(S)=h∈G and let x∈N be an integer such that
(stexp(G)(G)−i)x≡1(modexp(G)). |
Such integer x exists because gcd(stexp(G)(G)−i,exp(G))=1. Let
S′=−(xh)+S. |
Since σ(S′)=σ(S)−(stexp(G)(G)−i)xh=0, we obtain that S′ is a zero-sum sequence of length stexp(G)(G)−i. Next we prove that S′ has no zero-sum subsequence of length texp(G). Assume to the contrary that T′ is a zero-sum subsequence of S′ with |T′|=texp(G). Then σ(T′)+texp(G)(xh)=0. It follows that T=(xh)+T′ is a zero-sum subsequence of S with |T|=texp(G), yielding a contradiction to the definition of S. So S′ has no zero-sum subsequence of length texp(G). It follows that s′texp(G)(G)>stexp(G)(G)−i, and we are done.
Moreover, if gcd(stexp(G)(G)−1,exp(G))=1, then s′texp(G)(G)>stexp(G)(G)−1. By (1.1), we obtain that s′texp(G)(G)≤stexp(G)(G). Therefore, s′texp(G)(G)=stexp(G)(G).
We need the following lemmas to prove Theorem 1.3.
Lemma 2.1. [9,Proposition 4.1] Suppose t≥2, then stn(Z2n)=tn+2n−2.
Lemma 2.2. [11,Theorem 5.8.3] Let G=Zm⊕Zn with 1≤m∣n. Then s(G)=2m+2n−3.
Lemma 2.3. [20,Theorem 5.9] s2t(Zd2)=2t+d for d<2t.
Proof of Theorem 1.3. (1). Let G=Z2n. Suppose t≥2. By Lemma 2.1, we have that stn(G)=tn+2n−2. Since gcd(n,3)=1, we infer that gcd(stn(G)−1,n)=1. It follows from Theorem 1.2 that s′tn(G)=stn(G)=tn+2n−2.
(2). Let G=Zm⊕Zn. By Lemma 2.2, we have that s(G)=2m+2n−3. Since gcd(2m−i,n)=1 for some integer i≥4, we infer that gcd(s(G)−(i−3),exp(G))=1. By Theorem 1.2, we obtain that s′(G)≥s(G)−(i−3)+1=2m+2n−(i−1).
If i=4, we infer that gcd(s(G)−1,exp(G))=1. By Theorem 1.2, we obtain that s′(G)=s(G)=2m+2n−3.
(3). Let G=Zd2. Since d<2t, by Lemma 2.3, we have that s2t(G)=2t+d. Since d is even, we obtain that gcd(2t+d−1,2)=1, i.e. gcd(s2t(G)−1,exp(G))=1. By Theorem 1.2, we obtain that s′2t(G)=s2t(G)=2t+d.
In this section, we study some cases when s′texp(G)(G)≠stexp(G)(G).
Proof of Theorem 1.5. (1). We proceed by induction on k. If k=k1, then by the hypothesis of the theorem we have s′(Zdnk1)≤s(Zdnk1)−i.
Suppose that the theorem is true for k−1≥k1. We will show that s′(Zdnk)≤s(Zdnk)−i. Let S be a zero-sum sequence over Zdnk with |S|=s(Zdnk)−i=c(nk−1)+1−i. It suffices to show that S contains a zero-sum subsequence of length nk. Let
ϕ: Zdnk → Zdnk−1 |
be the natural homomorphism with kerϕ≅Zdn. Then ϕ(S) is a zero-sum sequence over Zdnk−1 with |ϕ(S)|=c(nk−1)+1−i=c(n−1)×nk−1+c(nk−1−1)+1−i>c(nk−1−1)+1−i. By the assumption, we have s′(Zdnk−1)≤c(nk−1−1)+1−i. So we can find a subsequence S1 of S such that ϕ(S1) is a zero-sum sequence over Zdnk−1 of length nk−1. It follows that ϕ(SS−11) is a zero-sum sequence over Zdnk−1 with |ϕ(SS−11)|=c(nk−1)+1−i−nk−1=(c(n−1)−1)×nk−1+c(nk−1−1)+1−i>c(nk−1−1)+1−i (n>1). Then we can find a subsequence S2 of SS−11 such that ϕ(S2) is a zero-sum sequence over Zdnk−1 of length nk−1. Repeating the above procedure, one can find c(n−1)+1 disjoint zero-sum subsequences ϕ(S1),…,ϕ(Sc(n−1)+1) of ϕ(S) such that |ϕ(S1)|=⋯=|ϕ(Sc(n−1)+1)|=nk−1. Since ϕ(σ(Si))=σ(ϕ(Si))=¯0∈Zdnk−1, we infer that σ(Si)∈kerϕ≅Zdn for i=1,…,c(n−1)+1. Let
T=σ(S1)⋅…⋅σ(Sc(n−1)+1). |
Then T is a sequence over kerϕ≅Zdn. By the hypothesis of the theorem, we have s(Zdn)=c(n−1)+1. So T has a zero-sum subsequence of length n. Without loss of generality we may assume that σ(S1)σ(S2)⋅…⋅σ(Sn) is a zero-sum subsequence of T over kerϕ≅Zdn. Since σ(S1)+σ(S2)+⋯+σ(Sn)=0∈kerϕ⊆Zdnk and |S1S2⋅…⋅Sn|=|ϕ(S1)ϕ(S2)⋅…⋅ϕ(Sn)|=nk, we obtain that S1S2⋅…⋅Sn is a zero-sum subsequence of S of length nk. It follows that s′(Zdnk)≤s(Zdnk)−i, and we are done.
(2). Let G=Zm⊕Zn with 1≤m∣n and H=Zd⊕Zd with d∣m. By Lemma 2.2, we have s(G)=2m+2n−3. Let S be a zero-sum sequence over G with |S|=s(G)−i=2m+2n−3−i. It suffices to show that S contains a zero-sum subsequence of length n. Let
ϕ: G → H |
be the natural homomorphism with kerϕ≅G/H=Zmd⊕Znd. By the assumption, we have s′(H)≤4d−3−i. Since ϕ(S) is a zero-sum sequence over H with |ϕ(S)|=2m+2n−3−i=(2md+2nd−4)d+4d−3−i, similar with (1), we can find 2md+2nd−3 disjoint zero-sum subsequences ϕ(S1),…,ϕ(S2md+2nd−3) such that |ϕ(S1)|=⋯=|ϕ(S2md+2nd−3)|=d. By Lemma 2.2, we have s(G/H)=2md+2nd−3. So we can prove that S has a zero-sum subsequence of length n. It follows that s′(G)≤s(G)−i, and we are done.
In 2003, Gao and Thangadurai proved the following result.
Lemma 3.1. [8,Corollary 1.1] The pairs (2k,d), (3k,3) have Property D for any positive integers k and d.
We need the following results.
Lemma 3.2. (1) s(Zd2k)=2d(2k−1)+1 for every k≥1 and d≥1. (Harborth [16])
(2) s(Z33k)=9(3k−1)+1 for every k≥1. (Gao and Thangadurai [8])
Now we are in a position to prove Theorem 1.6.
Proof of Theorem 1.6. (1). We will prove s′(Zd2k)=2d(2k−1)+1 for k≤d−1. By (1.1) and Lemma 3.2.(1), we have s′(Zd2k)≤s(Zd2k)=2d(2k−1)+1. Let
W=∏a1,a2,…,ad∈{0,1}(a1,a2,…,ad)2k−1. |
Since k≤d−1, it is easy to check that W is a zero-sum sequence of length 2d(2k−1), and W contains no zero-sum subsequence of length 2k. It follows that s′(Zd2k)≥2d(2k−1)+1. Therefore, s′(Zd2k)=2d(2k−1)+1 for k≤d−1.
(2). Assume that k≥d. By (1.1) and Lemma 3.2.(1), we have s′(Zd2k)≤s(Zd2k)=2d(2k−1)+1. We first prove that s′(Zk2k)≤2k(2k−1). Let S be a zero-sum sequence over Zk2k with |S|=2k(2k−1). We need to prove that S contains a zero-sum subsequence of length 2k. Assume to the contrary that S contains no zero-sum subsequence of length 2k. Note that |S|=s(Zk2k)−1. By Lemma 3.1, we obtain that the pair (2k,k) has Property D. Therefore, S is of form T2k−1 for some sequence T with |T|=s(Zk2k)−12k−1=2k. Since 0=σ(S)=(2k−1)σ(T) and gcd(2k−1,2k)=1, we infer that σ(T)=0. Therefore, T is a zero-sum subsequence of S with |T|=2k, yielding a contradiction. So S contains a zero-sum subsequence of length 2k, and this proves that
s′(Zk2k)≤2k(2k−1)=s(Zk2k)−1. |
By Theorem 1.5, we have that s′(Zd2k)≤s(Zd2k)−1=2d(2k−1) for every k≥d. Since gcd(2d(2k−1)−1,2k)=gcd(s(Zd2k)−2,exp(Zd2k))=1, by Theorem 1.2, we obtain that
s′(Zd2k)>s(Zd2k)−2=2d(2k−1)−1. |
Therefore, s′(Zd2k)=2d(2k−1) for every k≥d.
(3). By Lemma 3.2.(2), we have s(Z33k)=9(3k−1)+1. Since (3k,3) has Property D, by using a similar argument as in (2), we can prove that s′(Z33k)=9(3k−1) for every integer k≥2.
In this section, we give some additional results. By (1.1), we have s′texp(G)(G)≤stexp(G)(G) for every finite abelian group G and every positive integer t. By Theorem 1.6, the equality s′texp(G)(G)=stexp(G)(G) does not always hold. A natural problem asks that
Problem 4.1. When do we have s′texp(G)(G)=stexp(G)(G)?
By Theorem 1.2, if gcd(stexp(G)(G)−1,exp(G))=1, then s′texp(G)(G)=stexp(G)(G). However, gcd(stexp(G)(G)−1,exp(G))=1 is not necessary for s′texp(G)(G)=stexp(G)(G). In this paper, we are able to prove the following result.
Theorem 4.2. Let G=Z2t2. Then s′2t(G)=s2t(G)=4t+1.
In order to prove Theorem 4.2, we need the following result due to Sidorenko [20].
Lemma 4.3. [20,Theorem 5.10] s2t(Z2t2)=4t+1.
Proof of Theorem 4.2. By (1.1) and Lemma 4.3, we have
s′2t(Z2t2)≤s2t(Z2t2)=4t+1. |
Next we need to prove s′2t(Z2t2)≥4t+1. We denote ej=(a1,a2,…,a2t) for every j=1,2,…,2t, where aj=1 and ai=0 for every i≠j. Let
T=02t−1e1⋅e2⋅…⋅e2t⋅(e1+e2+⋯+e2t). |
Then T is a zero-sum sequence with |T|=4t and T contains no zero-sum subsequence of length 2t. Hence, s′2t(Z2t2)≥4t+1. Therefore, s′2t(Z2t2)=4t+1.
Among other results, we can also determine some cases when s′texp(G)(G)<stexp(G)(G) holds.
Theorem 4.4. (1) If G=Zn with gcd(n,2)≠1, then s′tn(G)<stn(G) for every integer t≥1.
(2) If G=Z2n with 4∣n, then s′(G)<s(G).
(3) If G=Zm⊕Zn with 4∣m∣n, then s′(G)<s(G).
In order to prove Theorem 4.4, we need the following results.
Lemma 4.5. [5,Theorem 1.3] s′tn(Zn)=(t+1)n−ℓ+1 for every integer t≥1, where ℓ is the smallest integer such that ℓ∤n.
Lemma 4.6. [5,Theorem 1.4] s′(Z2n)=4n−ℓ+1, where ℓ is the smallest integer such that ℓ≥4 and ℓ∤n.
The following result is a consequence of the Erdős-Ginzburg-Ziv Theorem.
Lemma 4.7. Let t,n be two positive integers. Then stn(Zn)=(t+1)n−1.
Proof of Theorem 4.4. (1). By Lemma 4.5, we infer that s′tn(Zn)=(t+1)n−ℓ+1 for every integer t≥1, where ℓ is the smallest integer such that ℓ∤n. Since gcd(n,2)≠1, we infer that ℓ≥3. It follows that s′tn(Zn)≤(t+1)n−2. By Lemma 4.7, we have that s′tn(Zn)<stn(Zn).
(2). By Lemma 4.6, we infer that s′(Z2n)=4n−ℓ+1, where ℓ is the smallest integer such that ℓ≥4 and ℓ∤n. Since 4∣n, we infer that ℓ≥5. It follows that s′(Z2n)≤4n−4. By Lemma 2.2, we get that s′(Z2n)<s(Z2n). (3). Let H=Z24. By (2), we obtain that s′(H)≤s(H)−1. By Theorem 1.5, we infer that s′(Zm⊕Zn)<s(Zm⊕Zn).
We would like to thank the referees for their very carefully reading and very useful suggestions. This research was supported in part by the Fundamental Research Funds for the Central Universities (No. 3122019152).
All authors declare no conflicts of interest in this paper.
[1] |
N. Alon, S. Friedland, G. Kalai, Regular subgraphs of almost regular graphs, J. Combin. Theory Ser. B, 37 (1984), 79–91. https://doi.org/10.1016/0095-8956(84)90047-9 doi: 10.1016/0095-8956(84)90047-9
![]() |
[2] | C. Augspurger, M. Minter, K. Shoukry, P. Sissokho, K. Voss, Avoiding zero-sum sequences of prescribed length over the integers, Integers, 17 (2017), Paper No. A18, 13pp. |
[3] |
A. Bialostocki, P. Dierker, On the Erdős-Ginzburg-Ziv theorem and the Ramsey numbers for stars and matchings, Discrete Math., 110 (1992), 1–8. https://doi.org/10.1016/0012-365X(92)90695-C doi: 10.1016/0012-365X(92)90695-C
![]() |
[4] |
A. Berger, An analogue of the Erdős-Ginzburg-Ziv Theorem over Z, Discrete Math., 342 (2019), 815–820. https://doi.org/10.1016/j.disc.2018.11.018 doi: 10.1016/j.disc.2018.11.018
![]() |
[5] |
A. Berger, D. Wang, Modified Erdős-Ginzburg-Ziv constants for Z/nZ and (Z/nZ)2, Discrete Math., 342 (2019), 1113–1116. https://doi.org/10.1016/j.disc.2018.12.024 doi: 10.1016/j.disc.2018.12.024
![]() |
[6] |
J. Bitz, S Griffith, X. He, Exponential lower bounds on the generalized Erdős-Ginzburg-Ziv constant, Discrete Math., 343 (2020), 112083, 4pp. https://doi.org/10.1016/j.disc.2020.112083 doi: 10.1016/j.disc.2020.112083
![]() |
[7] | P. Erdős, A. Ginzburg, A. Ziv, Theorem in the additive number theory, Bull. Res. Council Israel, 10 (1961), 41–43. |
[8] |
W. Gao, R. Thangadurai, On the structure of sequences with forbidden zero-sum subsequences, Colloq. Math., 98 (2003), 213–222. https://doi.org/10.4064/cm98-2-7 doi: 10.4064/cm98-2-7
![]() |
[9] |
W. Gao, D. Han, J. Peng, F. Sun, On zero-sum subsequences of length kexp(G), J. Combin. Theory Ser. A, 125 (2014), 240–253. https://doi.org/10.1016/j.jcta.2014.03.006 doi: 10.1016/j.jcta.2014.03.006
![]() |
[10] |
W. Gao, S. Hong, J. Peng, On zero-sum subsequences of length kexp(G) II, J. Combin. Theory Ser. A, 187 (2022), 105563. https://doi.org/10.1016/j.jcta.2021.105563 doi: 10.1016/j.jcta.2021.105563
![]() |
[11] | A. Geroldinger, F. Halter-Koch, Non-Unique Factorizations. Algebraic, Combinatorial and Analytic Theory, Pure and Applied Mathematics, vol. 278. Chapman & Hall/CRC, Boca Raton, FL, 2006. https://doi.org/10.1201/9781420003208 |
[12] |
B. Girard, W.A. Schmid, Direct zero-sum problems for certain groups of rank three, J. Number Theory, 197 (2019), 297–316. https://doi.org/10.1016/j.jnt.2018.08.016 doi: 10.1016/j.jnt.2018.08.016
![]() |
[13] |
B. Girard, W.A. Schmid, Inverse zero-sum problems for certain groups of rank three, Acta Math. Hungar., 160 (2020), 229–247. https://doi.org/10.1007/s10474-019-00983-w doi: 10.1007/s10474-019-00983-w
![]() |
[14] |
D. Han, H. Zhang, On generalized Erdős-Ginzburg-Ziv constants of Crn, Discrete Math., 342 (2019), 1117–1127. https://doi.org/10.1016/j.disc.2018.12.018 doi: 10.1016/j.disc.2018.12.018
![]() |
[15] |
D. Han, H. Zhang, Zero-sum invariants on finite abelian groups with large exponent, Discrete Math., 342 (2019), 111617, 7pp. https://doi.org/10.1016/j.disc.2019.111617 doi: 10.1016/j.disc.2019.111617
![]() |
[16] |
H. Harborth, Ein Extremalproblem für Gitterpunkte, J. Reine Angew. Math., 262 (1973), 356–360. https://doi.org/10.1515/crll.1973.262-263.356 doi: 10.1515/crll.1973.262-263.356
![]() |
[17] | G. Hegedűs, An improved exponential upper bound for the Erdős-Ginzburg-Ziv constant, Integers, 20 (2020), Paper No. A22, 5pp. |
[18] |
E. Naslund, Exponential bounds for the Erdős-Ginzburg-Ziv constant, J. Combin. Theory Ser. A, 174 (2020), 105185, 19pp. https://doi.org/10.1016/j.jcta.2019.105185 doi: 10.1016/j.jcta.2019.105185
![]() |
[19] |
J. Oh, Q. Zhong, On Erdős-Ginzburg-Ziv inverse theorems for dihedral and dicyclic groups, Israel J. Math., 238 (2020), 715–743. https://doi.org/10.1007/s11856-020-2036-6 doi: 10.1007/s11856-020-2036-6
![]() |
[20] |
A. Sidorenko, On generalized Erdős-Ginzburg-Ziv constants for Zd2, J. Combin. Theory Ser. A, 174 (2020), 150254, 20pp. https://doi.org/10.1016/j.jcta.2020.105254 doi: 10.1016/j.jcta.2020.105254
![]() |
1. |
Alexander Sidorenko,
Modified Erdős–Ginzburg–Ziv Constants for Zd2 ,
2023,
39,
0911-0119,
10.1007/s00373-023-02709-w
|